CORROTION RATE AND MORPHOLOGY OF POROUS METAL ALLOY Mg-Ca-Zn WITH CaCO3 AS FOAMING AGENT - Aprilia Erryani; Franciska Pramuji Lestari; Dhyah Annur; Muhammad Ikhlasul Amal; Ika Kartika (Pusbindiklat - LIPI, 2018)
Magnesium alloy is a material that has been developed as a biodegradable implant material in orthopedic applications. Magnesium alloys have good biocompatibility, biodegradability, and good mechanical properties which make them have the potential to be used as a biomedical material. The main objective of this paper is to investigate corrotion rate and morphology after corrotion of biocompatibility of implant-based alloys Mg-Ca-Zn with CaCO3 as a foaming agent. Mg-Ca-Zn Alloy was made by the method of powder metallurgy with the addition of CaCO3 as a foaming agent with three variations of composition (96Mg-Ca-3Zn-CaCO3, 91Mg-Ca-3Zn-5 CaCO3, and 86Mg-Ca-3Zn-10 CaCO3 wt%). Sintering process was carried out at 600 °C and 650 °C with a holding time of five hours. Corrosion test was performed using G750 Gamry Instrument in accordance with ASTM standard G5-94. Simulated body fluid electrolyte used is Hank's solution with a pH value of 7.4 and a temperature of 37 °C. Then the analysis of the microstructure after corrosion test was conducted using scanning electron microscopy (JEOL, JSM-6390A Japan) equipped with energy dispersive spectrometry data (EDS). Alloy corrosion rate of Mg-Ca-Zn-CaCO3 increases with the amount of CaCO3 in the alloy and the temperature rise in the sintering. From the test results, the smallest corrosion rate is in the alloy 91Mg-Ca-3Zn-CaCO3 at 600 °C sintering (58.3045 mpy) and the highest occurs in alloy 86Mg-Ca-3Zn-10CaCO3 at 650 °C sintering (91.4007 mpy). Surface morphology of the alloy after the corrosion process is the type of volcano. This localized corrosion occurs where an electrochemical reaction takes place to form a distinctive structure with a circle and a hole in the middle.